Stability analysis for SiC grinding based upon harmonic wavelet and Lipschitz exponent. Issue 5 (3rd September 2019) - Li, Qing; Ji, Xia; Yang, Jianguo; Liang, Steven Y.
Abstract: In order to effectively identify the stability degree of grinding and obtain better surface integrity of machined workpiece in grinding application, in this paper, a quantitative assessment approach based on harmonic wavelet and Lipschitz exponent is proposed, using silicon carbide as an example. To begin with, the Lipschitz exponent is defined and calculated by harmonic wavelet modulus maxima (HWMM) and linear regression algorithm, respectively. Then the Kurtosis based on Lipschitz exponent (KLE) is defined as a quantitative indicator. In grinding experiment, the acceleration signals and grinding force signals of the X / Y directions are selected, and experimental parameters including wheel speed, workpiece speed and grinding depth are employed to investigate the grinding stability in grinding stage. Experimental results show that the grinding stability is relatively worse at low wheel speed, low-high workpiece speed and large grinding depth in terms of KLE index, which may provide a new guidance to explore optimized grinding parameters and thus obtain good surface integrity in engineering applications.